2020
DOI: 10.2174/1568026620666200508082615
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin/Orphanin FQ Peptide Receptor-Related Ligands as Novel Analgesics

Abstract: : Despite similar distribution patterns and intracellular events observed in the nociceptin/orphanin FQ peptide (NOP) receptor and other opioid receptors, NOP receptor activation displays unique pharmacological profiles. Several researchers have identified a variety of peptide and non-peptide ligands to determine the functional roles of NOP receptor activation and observed that NOP receptorrelated ligands exhibit pain modality-dependent pain processing. Importantly, NOP receptor activation results in anti-noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 149 publications
0
23
0
Order By: Relevance
“…In this study, we characterized the intrinsic activity of chemically diverse NOP agonists in various G protein-mediated functional assays (GTPγS binding, cAMP inhibition and GIRK activation) and characterized agonist-induced receptor trafficking by measuring ligand-induced NOP receptor phosphorylation of selected residues, arrestin recruitment and receptor internalization. Targeting the NOP receptor has been proposed by us and others as an approach to reduce the side effects of MOR agonists (Bird and Lambert, 2015;Gunther et al, 2018;Kiguchi et al, 2020a;Kiguchi et al, 2020b;Toll et al, 2009). Using an array of ligands, we showed that NOP agonists with varying functional selectivity towards the MOR receptor, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we characterized the intrinsic activity of chemically diverse NOP agonists in various G protein-mediated functional assays (GTPγS binding, cAMP inhibition and GIRK activation) and characterized agonist-induced receptor trafficking by measuring ligand-induced NOP receptor phosphorylation of selected residues, arrestin recruitment and receptor internalization. Targeting the NOP receptor has been proposed by us and others as an approach to reduce the side effects of MOR agonists (Bird and Lambert, 2015;Gunther et al, 2018;Kiguchi et al, 2020a;Kiguchi et al, 2020b;Toll et al, 2009). Using an array of ligands, we showed that NOP agonists with varying functional selectivity towards the MOR receptor, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…10 The NOP receptor shares approximately 60 percent homology in the structural components of classical opioid (MOP, DOP, and KOP) receptors. 11,12 Unlike classical opioid receptors, the NOP receptor possesses little or no affinity for opioid peptides, eg, β-endorphin and enkephalin, or morphine-like compounds. One year after the identification of the NOP receptor, the natural ligand for NOP receptor was identified.…”
Section: The Nop Receptormentioning
confidence: 99%
“…The activated NOP receptor couples to Gi/o-proteins to inhibit adenylate cyclase, decreasing Ca 2+ conductance and increasing K + conductance, among other intracellular processes. 11,12 Once activated, NOP receptors reduce afferent neuronal excitability and thereby modulate neurotransmitter release from axon terminals, including γ-amino butyric acid, glutamate, dopamine, and norepinephrine.…”
Section: The Nop Receptormentioning
confidence: 99%
See 2 more Smart Citations